(untitled) (Heritage, 2025)
Internally displaced persons from Kosovo and Metohija represent one of the most vulnerable social groups in the post-conflict period, with women among them facing particularly complex and often invisible forms of legal and social exclusion. Although the Constitution of the Republic of Serbia guarantees equality and the protection of fundamental rights for all citizens, in practice, the constitutional protection of displaced women proves to be insufficiently effective. This paper analyzes the legal status of internally displaced persons from a gender perspective, focusing on access to justice, property and family rights, protection from violence, social security, and the right of return. The aim of the paper is to contribute, through constitutional analysis and a gender-sensitive model, to understanding the position of internally displaced persons as a key issue within the overall policy towards Kosovo and Metohija.